Tillage and fertilizer effect on maize and soybean yields in the Guinea savanna zone of Ghana - Buah, Saaka S.J.; Ibrahim, Hachim; Derigubah, Mavis; Kuzie, Martin; Segtaa, James Vuuro; Bayala, Jules; Zougmoré, Robert B.; Ouédraogo, Mathieu (Springer, 2017)
Background: The most limiting factors for sustainable maize production in smallholder farming systems of sub-Saharan Africa, especially the savanna agro-ecological zone, are erratic rainfall pattern and low soil fertility.